Inelastic displacement ratios for structures with foundation flexibility - Eser, Muberra; Aydemir, Cem; Ekiz, Ibrahim (SPRINGER, 2012)
Inelastic displacement ratios have been generally investigated for fixed-base systems without taking into consideration soil structure interaction. In this study, inelastic displacement ratios are investigated for SDOF systems with period range of 0.1-3.0 s with elastoplastic behavior considering soil structure interaction for 64 different earthquake motions recorded on different site conditions such as rock, stiff soil, soft soil and very soft soil. Soil structure interacting systems are modeled with effective period, effective damping and effective ductility values differing from fixed-base case. For inelastic time history analyses, Newmark method for step by step time integration was adapted in an in-house computer program. Results are compared with those calculated for fixed-base case. A new equation is proposed for inelastic displacement ratio of interacting system as a function of structural period of interacting system ((T)over tilde), ductility ratio (mu) and period lengthening ratio ((T)over tilde/T)]. The fitness of the regressed function of the inelastic displacement factor is shown in figures. The regressed equation for (C)over tilde(mu) should be useful in estimating the inelastic deformation of structure where the global ductility capacity can be estimated.
Keywords: soil-structure interaction; inelastic displacement ratio; ductility demand; seismic analysis; SDOF SYSTEMS; SITES; DESIGN; Engineering